2014
DOI: 10.1093/trstmh/tru096
|View full text |Cite
|
Sign up to set email alerts
|

Non-bacterial etiologies of diarrheal diseases in Afghanistan

Abstract: Non-bacterial pathogens were identified that could enable health officials to adopt more effective treatment and control measures for diarrhea in Afghanistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One hundred and sixty-five publications were included in the qualitative assessment ( Figure 2). The countries and number of associated references from which published data were obtained are: Afghanistan (1), 12 Bahrain (3), [13][14][15] Egypt (17), [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Iran (37), Iraq (3), 41,69,70 Jordan (9), [71][72][73][74][75][76][77][78][79] Kuwait (2), 80,81 Lebanon (3), [82][83][84] Libya (5), [85][86][87][88][89] Morocco (9), [90][91][92][93][94]…”
Section: Resultsmentioning
confidence: 99%
“…One hundred and sixty-five publications were included in the qualitative assessment ( Figure 2). The countries and number of associated references from which published data were obtained are: Afghanistan (1), 12 Bahrain (3), [13][14][15] Egypt (17), [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Iran (37), Iraq (3), 41,69,70 Jordan (9), [71][72][73][74][75][76][77][78][79] Kuwait (2), 80,81 Lebanon (3), [82][83][84] Libya (5), [85][86][87][88][89] Morocco (9), [90][91][92][93][94]…”
Section: Resultsmentioning
confidence: 99%
“…This impact would be increasingly lower if more cases are of bacterial or non-rotavirus viral origin. The etiology of diarrhea in Afghanistan is not well understood; a study of nonbacterial diarrhea in Kabul did find that over three-quarters of the cases had rotavirus [24], although the overall proportion of diarrhea due to nonbacterial causes was not mentioned and the study sites were a convenience sample within one city in Afghanistan, whose populace is still predominantly rural. Further research should investigate the etiology of diarrhea in Afghanistan and changes in diarrhea incidence once the rotavirus vaccine has been more fully implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been done on rotavirus in different countries of the world. About 5% of children's deaths in Afghanistan are related to rotavirus, which shows the necessity of continuous research on this disease (16). The findings of this study showed that more than 50% of children with diarrhea referred to Indira Gandhi Children's Health Hospital were related to rotavirus has not yet improved and requires special attention from the authorities (17).…”
Section: Discussionmentioning
confidence: 83%